Fluid dynamics. - Ruban, A. I. (Anatoliĭ Ivanovich), 1943- (Oxford University Press, 2018)
The notion of the boundary layer was introduced to describe thin viscous layers that form on a rigid body surface in otherwise inviscid flow of a fluid with small viscosity. The book begins with the classical theory of the boundary-layer flows. However, its focus is on recent results of the theory invaluable in describing fluid-dynamics phenomena.